2021
DOI: 10.3390/rel12121098
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Islam and Buddhism: A Multicultural Society Perspective

Abstract: In this article, two great world religions, Islam and Buddhism, are compared. The purpose is to highlight similarities and differences between the two religions. Additionally, this article aims to project elements and teachings that are deemed important by their followers. A neutral stance on their beliefs is especially important in a multicultural society. The study was conducted to promote the harmony and betterment of Malaysian society, and the nation at large; a value process of understanding of each relig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The impact of Islam and Buddhism on individuals’ lifestyles and health-related behaviors has been significant. Muslim women exhibited a profound conviction in the authority of God (Allah), whereas Buddhist women commonly invoked their karma [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of Islam and Buddhism on individuals’ lifestyles and health-related behaviors has been significant. Muslim women exhibited a profound conviction in the authority of God (Allah), whereas Buddhist women commonly invoked their karma [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Muslim women in our study had a strong belief in the influence of God (Allah), whereas Buddhist women tended to refer to their own karma. Yew et al described the important aspect of Islam as the belief in a God or Allah [ 30 ]. The deeds of individuals will be devoted to God, and this determines the life and destiny of each person.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 97.5% of the 205 research subjects reported never having encountered conflicts A profound comprehension of the importance of tolerance enables religious practitioners to foster peace within their nation and state. The occurrence of numerous incidents of intolerance does not necessarily indicate the prevalence of intolerance and conservatism in religious beliefs (Holmes, 2021;Wolloch, 2022;Saltelli et al, 2019).…”
Section: Understanding the Tolerance Valuesmentioning
confidence: 99%